Behavioral Assessment of Patients With Disorders of Consciousness. Issue 1 (January 2022) - Fitzpatrick-DeSalme, Eileen; Long, Angela; Patel, Ferzeen; Whyte, John
Abstract : Summary: Brain injury resulting in coma may evolve into a prolonged disorder of consciousness, including the vegetative and minimally conscious states. Early detection of emerging consciousness has positive prognostic significance, and improvement in consciousness at any point may indicate the potential for meaningful communication and environmental control. Despite the importance of accurate assessment of consciousness, research indicates that as many as 40% of patients with a disorder of consciousness may be assessed incorrectly. Assessment of consciousness is challenging for many reasons, including the fact that consciousness cannot be measured directly but must be inferred from patterns of behavioral activity, that many patients have confounding deficits and treatments that may mask consciousness, and that patient performance may be highly variable over time. In this manuscript, we discuss strategies for optimizing patient status during assessment and review a number of structured assessment approaches that can be used. The available assessment techniques vary in their length and cost, and the expertise required to use them. Which of these approaches is most applicable to a given acute or subacute setting will vary with the volume of patients with a disorder of consciousness and the available resources. Importantly, lack of consciousness in the acute setting should not be used to justify the withdrawal of care or denial of rehabilitation services.